The Role of the British Advisor Charles Belgrave in the Making of the Modern State of Bahrain (1926 - 1957): A Historical Study - AlMezaal, Sharaf Mohamed Ali (Journal of Humanities & Social Sciences, 2023)
This study aims to reveal the role of Sir Charles Belgrave, the British advisor to the Government of Bahrain (1926 - 1957), in establishing the modern state of Bahrain, based on the relevant historical documents, to reveal the mechanisms of political decision-making during that period, and to link the decisions with internal and external developments. The study was based on a number of historical sources, and concluded that Belgrave played a positive political role in building the modern state of Bahrain, and that he, as an advisor, was a government employee who did not act without prior permission from the ruling authority, but the broad administrative powers granted to him in running the affairs of state made him believe that he is the absolute decision maker. In addition, the decisions taken by Sir Belgrave were not individual, but came as a result of the interaction of the influence of internal forces; namely the ruling authority, the leaders of the Bahraini national movement, and external forces; namely the British colonial forces in the Arabian Gulf Region.
Keywords: Charles Belgrave; British Chancellor; British Colonialism; Rulers of Bahrain; State of Bahrain